ARABICA COFFEE PROCESSED PRODUCT DEVELOPMENT STRATEGY IN CENTRAL ACEH DISTRICT - Fadli; Emmia Tambarta Kembaren; Khairul Akbar; Aulia Rahman; Ahmad Alwi Piliang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Gayo coffee is quite famous in the world because it has a distinctive aroma and enjoyment and if it is cupped or taste tested . Aspects of coffee marketing can be viewed in terms of the type of commodity, actors, supply and demand. In general, the types of coffee marketing products are: (a) coffee grain /labui; (b) arabica coffee beans; (c) coffee grounds, and (d) other processed products. Central Aceh Regency generally produces coffee in the form of Arabica coffee beans (Green bean) while nowadays, the conditions of competition are getting tighter where each country develops their coffee processed products. The strategy for developing Arabica coffee commodities today is expected to be no longer how to increase production, but how a commodity can be processed so that added value is obtained from the processing process. The development of added value in coffee commodities is expected to produce diversified processed coffee products, such as roasted coffee, instant coffee, coffee mix, decaffeinated coffee, soluble coffee, coffee beer (coffee beer), ice coffee which has an important meaning, because it can become a leading commodity that have high competitiveness in the international market. This research was conducted in Central Aceh District. This is because Central Aceh Regency is the main location for processing coffee products in Aceh Province . The research method used is descriptive quantitative research method. The data collection method used was in-depth interviews with several key persons, namely: the trade department, the agriculture office, coffee expert staff, Gayo arabica coffee farmers and four coffee agroindustry green been and coffee powder which has the largest export quota in Bener Meriah Regency, namely KBQB Baburrayyan, Cooperative Oro Coffee, and PT Olam Coffee. The data analysis method used to calculate the added value is the Hayami method. This research resulted in TKT 1 with the output target in the form of (1) scientific publications in index international research journals crossreff with the status accepted, (2) HKI research reports with the status granted, (3) publication of activities in print or online media.